Underage Marriage in Maqashid Sharia Review: Reconstructing the Understanding of Contemporary Islamic Law - Rohayati, Dede (Fast in Social Sciences, 2025)
Underage marriage is still a concerning phenomenon in Indonesia despite the regulation of Law No. 16 of 2019 which sets a minimum age limit of 19 years. This study aims to analyze the law of underage marriage in the perspective of maqashid sharia and formulate a reconstruction of a more contextual understanding of contemporary Islamic law. The research uses a juridical-normative method with an analytical qualitative-descriptive approach. Primary data sources include the Qur'an, Hadith, classical and contemporary fiqh books, and laws and regulations. The data analysis technique uses the ushul fiqh approach with the maqashid sharia theoretical framework of Imam Ash-Syatibi. The results show that underage marriage is contrary to the fundamental principles of maqashid sharia, specifically: (1) hifdzun nafs because it threatens the physical and mental health of children; (2) hifdzun 'aql because it inhibits the right to education and cognitive development; (3) hifdzun nasl because it increases the risk of mother-child mortality and stunting; and (4) it fails to realize the purpose of marriage, namely sakinah, mawaddah, warahmah. This study concludes that although there is no explicit prohibition in the text, early marriage must be prevented because its madarat is greater than its maslahat. The reconstruction of contemporary Islamic legal understanding must be based on a contextual approach that integrates maqashid sharia with the findings of modern science to realize the true benefit for children.